when comes to factoring u need to make one side 0
so its 5x^2 + 7x -6=0
then u factor it out (5x+2 )(x-3 ) so then u need to make x 0 so
x= 3, and -2/5
2006-12-03 12:31:03
·
answer #1
·
answered by azn boy 2
·
0⤊
0⤋
Put the 6 on the other side and start factoring
5x^2 + 7x - 6 = 0
(5x+?) (x + ?) is what you gotta figure out.
(5x - 3) (x + 2) = 0 is what you got by factoring
Because
5x * x = 5x^2
5x * 2 + x * -3 = 10x - 3x = 7x
-3 * 2 = -6
For the equation to = 0, x = 3/5 or -2
2006-12-03 20:27:18
·
answer #2
·
answered by Roman Soldier 5
·
0⤊
1⤋
You'd subtract 6, and bring it to the other side, so it would look like this:
5x^2+7x-6=0
Then, from there, you would factor it:
(5x-3) (x+2) = 0
Set each term equal to zero:
5x-3=0, x+2=0
Then, solve:
x=3/5 , x=-2
So your two answers are x= 3/5, -2
2006-12-03 20:25:17
·
answer #3
·
answered by chococat 4
·
0⤊
0⤋
5x^2 + 7x = 6
5x^2 + 7x - 6 = 0
(x + 2)(5x - 3) = 0
here is how you can get it when you can't figure out how to factor
x = (-b ± sqrt(b^2 - 4ac))/(2a)
x = (-7 ± sqrt(7^2 - 4(5)(-6)))/(2(5))
x = (-7 ± sqrt(49 + 120))/10
x = (-7 ± sqrt(169))/10
x = (-7 ± 13)/10
x = (-20/10) or (6/10)
x = -2 or (3/5)
ANS : (x + 2)(5x - 3)
2006-12-03 20:55:55
·
answer #4
·
answered by Sherman81 6
·
0⤊
1⤋